Differences in Bordetella pertussis DNA load according to clinical and epidemiological characteristics of patients with whooping cough. Issue 4 (April 2016) - Brotons, Pedro; de Paz, Hector D.; Toledo, Diana; Villanova, Marta; Plans, Pedro; Jordan, Iolanda; Dominguez, Angela; Jane, Mireia; Godoy, Pere; Muñoz-Almagro, Carmen; ,
Summary: Objective: To identify associations between nasopharyngeal Bordetella pertussis DNA load and clinical and epidemiological characteristics and evaluate DNA load prognostic value in pertussis severity. Methods: Prospective observational multi-centre study including nasopharyngeal samples positive to pertussis DNA by real-time PCR collected from children and adult patients in more than 200 health centres of Catalonia (Spain) during 2012–2013. Results: B. pertussis load was inversely correlated with age (rho = −0.32, p < 0.001), time to diagnosis (rho = −0.33, p < 0.001) and number of symptoms (rho = 0.13, p = 0.002). Median bacterial load was significantly higher in inpatients versus outpatients (4.91 vs. 2.55 log10 CFU/mL, p < 0.001), patients with complications versus those without (6.05 vs. 2.82 log10 CFU/mL, p < 0.001), disease incidence in summer and autumn versus spring and winter (3.50 vs. 2.21 log10 CFU/mL, p = 0.002), and unvaccinated-partially vaccinated patients versus vaccinated (4.20 vs. 2.76 log10 CFU/mL, p = 0.004). A logistic regression model including bacterial load and other candidate prognostic factors showed good prediction for hospital care (AUC = 0.94) although only age and unvaccinated status were found to be prognostic factors. Conclusions: We observed strong positive associations of nasopharyngeal bacterial load with severity outcomes of hospitalisation and occurrence of complications. Bacterial load and other independent variables contributed to an accurate prognostic model for hospitalisation. Highlights: B. pertussis DNA load was inversely correlated with age, time since first symptom onset, and number of symptoms presented. B. pertussis DNA load showed significant differences by hospital or outpatient care, seasonality, and vaccination status. Age and vaccination status were found to be prognostic factors for hospitalisation due to B. pertussis infection.